What Does Successful Aging Sound like? Profiling Communication about Aging. (1st October 2015) - Gasiorek, Jessica; Fowler, Craig; Giles, Howard
Abstract: We draw on the recently developed communicative ecology model of successful aging (CEMSA) to examine how adults communicate about aging and how these communication patterns relate to experiences of successful aging. Using latent class analysis across 2 datasets collected in New Zealand and the United States, we identify 3 distinct classes of agers (disengaged, engaged, and bantering) defined by different profiles of communication behavior. Across samples, an engaged profile was generally associated with the most positive experiences of aging, whereas a disengaged profile was associated with the least positive experiences, although these differences were surprisingly small. Our results highlight the diverse ways in which individuals communicatively engage with the process of aging and experience aging as positive and successful.